Wiman-type inequality for functions analytic in a polydisc - Kurylyak, A. O.; Skaskiv, O. B.; Shapovalovs’ka, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We prove an analog of Wiman-type inequality for analytic functions in a polydisc D^p = {z C^p : |z_j| < 1, j { 1, . . . ,p} } , p N. The obtained inequality is sharp.